Persepsi Masyarakat Terhadap Standar Pelayanan Paspor Pada Kantor Imigrasi Kelas 1 Manado Menurut Undang-Undang Nomor 25 Tahun 2009 - Sentinuwo, Endrow Alfin; Lumolos, Johny; Areros, William A (JURNAL ILMIAH SOCIETY, 2016)
Public services can not be separated from issues of public interest, which became the origin of the emergence of the term public service. The globalization of information technology for carrying all agencies, the Institute, the Agency, the Department and the Office of Government towards changes on attitudes about how to provide public services effectively and efficiently. Rapid technological advances have led to a huge influence on all areas, namely in the information technology services to a government agency. This research is located at the Immigration Office Class 1 Manado is one of his duties is a service passport, service passport to analyze the terms of Law No. 25 of 2009 on public services. This study used qualitative research methods. From the results of research on public perception inside the passport is quite good but there are still things considered less.